Analysis of ploidy level of Artemisia annua L. based on flow cytometry and confocal laser scanning microscopy (Bangladesh Journal of Botany, 2021)
Eighty nine Artemisia samples treated with different concentrations of colchicine were used as breeding samples, with diploid Artemisia as the control. The ploidy levels of samples were determined by flow cytometry and confocal laser scanning microscopy (CLSM). An analysis of the flow cytometry results identified three suspected tetraploid plants and seven suspected triploid plants. The results of this study may be useful for breeding new Artemisia lines.